Menumbuhkan Minat Baca Anak Sebagai Bagian Dari Gerakan Literasi Nasional Melalui Pembuatan Pojok Baca Desa Karangan - Slamet Fauzan; Widyana Pramesti; Vicky Dwi Andika Putra (ABIDUMASY, 2021)
This community service is carried out by lecturers and students of the State University of Malang in Desa Karangan, Kecamatan Badegan, Kabupaten Ponorogo. There is one thing that is the focus of the community service work program in Desa Karangan, namely a low community literacy culture. The high number of school-age children is not accompanied by adequate literacy facilities. So that the literacy movement in Desa Karangan only relies on facilities and support from schools. This community service is carried out by lecturers and students of the State University of Malang in Desa Karangan, Kecamatan Badegan, Kabupaten Ponorogo. The creation of a reading corner aims to provide literacy facilities and form reading habits in order to increase reading interest as part of the literacy movement in Indonesia. The implementation of community activities begins with observation, then is carried out in stages, namely preparation, and evaluation. As an effort to establish reading in order to foster children's reading interest, assistance in reading activities is carried out in the reading corner of Desa Karangan, Kecamatan Badegan, Kabupaten Ponorogo. The result of this service is the growth of children's interest in reading in Desa Karangan, this can be seen from the high enthusiasm of the children during reading mentoring activities that are carried out every week. With this community service activity, it is hoped that it can foster children's interest in reading as an effort to activate the literacy movement in Indonesia.